2021
DOI: 10.3390/rs13081508
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Regression Models for Predicting Rice Yield and Protein Content Using Unmanned Aerial Vehicle-Based Multispectral Imagery

Abstract: Unmanned aerial vehicle-based multispectral imagery including five spectral bands (blue, green, red, red-edge, and near-infrared) for a rice field in the ripening stage was used to develop regression models for predicting the rice yield and protein content and to select the most suitable regression analysis method for the year-invariant model: partial least squares regression, ridge regression, and artificial neural network (ANN). The regression models developed with six vegetation indices (green normalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In this study, ENR is a relatively new machine learning algorithm being used for yield prediction. ENR combines the properties of ridge regression and LASSO ( Ogutu et al, 2012 ), both of which have been successfully applied to crop yield prediction ( Kang et al, 2021 ; Shafiee et al, 2021 ). The incorporation of multiple VIs adds collinearity to the models, and the ENR is robust to severe multicollinearity among the input features ( Ogutu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ENR is a relatively new machine learning algorithm being used for yield prediction. ENR combines the properties of ridge regression and LASSO ( Ogutu et al, 2012 ), both of which have been successfully applied to crop yield prediction ( Kang et al, 2021 ; Shafiee et al, 2021 ). The incorporation of multiple VIs adds collinearity to the models, and the ENR is robust to severe multicollinearity among the input features ( Ogutu et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the aim of this study was not crop phenotyping but instead to predict within-field variability in GY and PC using a single cultivar. Similar to this, Kang et al (2021) showed that data obtained with a five-band spectral camera mounted on a UAV in combination with machine learning (ML) allowed prediction of PC in a rice (Oryza sativa) cultivar with low error. As emphasized by Zhou et al (2021), it is essential to verify obtained results in such studies by considering a wide range of environments.…”
Section: Introductionmentioning
confidence: 54%
“…Similar to this, Kang et al. (2021) showed that data obtained with a five‐band spectral camera mounted on a UAV in combination with machine learning (ML) allowed prediction of PC in a rice ( Oryza sativa ) cultivar with low error. As emphasized by Zhou et al.…”
Section: Introductionmentioning
confidence: 71%
“…It strikes a balance between bias and variance, making it a useful tool in many real-world regression problems (Matdoan et al, 2021). Regression models for predicting rice yield and protein content using unmanned aerial vehicle-based multispectral imagery was employed by Kang et al (2021).…”
Section: Machine Learning Methodsmentioning
confidence: 99%